Dramatisasi Tipe Shot pada Iklan Pond’s for Men Edisi The Oily Warrior - Reza Oktavian (MEDIALOG: Jurnal Ilmu Komunikasi, 2023)
ABSTRACT Commercial advertising films, or television commercials (TVC), are made as attractive as possible with the aim of attracting viewers. The element of dramatization in advertising is needed and is closely related to the type of shot used. This study analyzes the dramatization of Pond's for Men advertisements for The Oily Warrior Edition, a facial care product specifically for men. Qualitative research method by analyzing the type of shot used to create dramatic effects. The results of this study provide an understanding that choosing the right type of shot in a scene will create a visual dramatization effect, which is an effective marketing strategy to create advertising films that attract the attention of viewers. Keywords: Dramatization, Shot, Shot Types, Television Commercial